Nano Online 2016
DOI: 10.1515/nano.bjneah.6.27
|View full text |Cite
|
Sign up to set email alerts
|

Green preparation and spectroscopic characterization of plasmonic silver nanoparticles using fruits as reducing agents

Abstract: Chemicals typically available in plants have the capability to reduce silver and gold salts and to create silver and gold nanoparticles. We report the preparation of silver nanoparticles with sizes between 10 and 300 nm from silver nitrate using fruit extract collected from pineapples and oranges as reducing agents. The evolvement of a characteristic surface plasmon extinction spectrum in the range of 420 nm to 480 nm indicates the formation of silver nanoparticles after mixing silver nitrate solution and frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…The most popular process among the bottom up methods might be the preparation of silver and gold nanoparticles in aqueous solution by the reduction of silver and gold salts using sodium citrate or sodium borohydride as reducing agent [ 9 ]. Recently it has been identified that also plant extracts have the capability to reduce silver and gold salts and to create silver and gold nanoparticles [ 10 19 ]. Many different chemical compounds are present in various parts of different plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most popular process among the bottom up methods might be the preparation of silver and gold nanoparticles in aqueous solution by the reduction of silver and gold salts using sodium citrate or sodium borohydride as reducing agent [ 9 ]. Recently it has been identified that also plant extracts have the capability to reduce silver and gold salts and to create silver and gold nanoparticles [ 10 19 ]. Many different chemical compounds are present in various parts of different plants.…”
Section: Introductionmentioning
confidence: 99%
“…Here we study the formation of silver nanoparticles using fruit extracts from oranges and pineapples and check their capability as enhancing plasmonic structures for surface enhanced Raman scattering (SERS). Extracts from these two fruits have been used for preparing silver and gold nanoparticles [ 12 , 15 19 ]. Here we explore the formation of nanoparticles by varying conditions in the preparation process such as ratios of the mixtures of silver nitrate and fruit extracts and the presence or absence of light.…”
Section: Introductionmentioning
confidence: 99%
“…The AgNPs were synthesised by the reduction of silver ions (Ag 2+ ) in to silver metal (Ag 0 ). Colour changes of reaction mixture indicate the biosynthesis of AgNPs and it was favoured by various reports [6, 9, 29]. Out of different tested concentrations of AgNO 3 , 5 mM showed maximum absorbance at 440 nm which confirmed the optimum concentration of AgNO 3 solution.…”
Section: Resultsmentioning
confidence: 57%
“…Phyto‐fabrication of metallic NPs by using plant extract as reducing agents is an alternate and advantageous over physical and chemical methods [5]. Several plants viz., Bougainvillea spectabilis, Azhadirachta indica, Crataegus douglasii, Prosopis farcta and Ananas comosus have been reported for efficient and rapid extra cellular synthesis of silver nanoparticles (AgNPs) [6–10].…”
Section: Introductionmentioning
confidence: 99%
“…Further, plant extracts mediated reduction of silver salts to AgNPs also provides capping for stability. Moreover, AgNPs synthesised from plant extract, have been reported to lack the ability towards aggregate formation and tend to remain dispersed even when aggregation is forced by any agent [5, 6]. Numerous studies have investigated plants extracts for the biosynthesis of AgNPs including, Cinnamon zeylancium bark, Coleus amboinicus Lour, Medicago sativa , Panax ginseng, Weissella oryza, Citrus sinensis peel, Terminalia arjuna .…”
Section: Introductionmentioning
confidence: 99%